Exercise-induced oxidative stress in overload training and tapering - Vollaard, N. B. J.; Cooper, C. E.; Shearman, J. P. (Medicine & Science in Sports & Exercise, 2006)
Tapering can be an effective way of enhancing performance after a period of intensive training, but the mechanisms for this ergogenic effect are unclear. It was hypothesized that overload training will increase oxidative stress through an accumulative effect of repeated high-intensity exercise, whereas tapering will improve the antioxidant defense system and alleviate oxidative stress.